Reversible suppression of sexual activity in tomcats with deslorelin implant - Novotny, R; Cizek, P; Vitasek, R; Bartoskova, A; Prinosilova, P; Janosovska, M (Theriogenology, 2012)
The aim of the study was to assess the efficacy of using a Gn-RH agonist implant (deslorelin, 4.7 mg, Suprelorin) to control sexual activity of male cats and reestablishment of sexual function after the implant removal 4 mo after placement. Using a control group (Group 1, n = 5), 22 domestic tomcats were given the implant subcutaneously in the region of the right shoulder blade and were then divided into two treatment groups. Animals in Group 2 (n = 14) were observed from the date of implant surgery and the observation lasted for 4 mo. In Group 3 (n = 8) all animals were monitored from the date of implant surgery. Then, after 4 mo, all implants were removed and the toms were observed for a further 4 mo. In all animals during their first visit and then in 1-mo intervals, changes in testosterone concentrations were assessed before (T0) and 4 h after (T4) human chorionic gonadotropin (HCG) administration and testis size was measured. In all tomcats, semen collection was performed, using an electroejaculator, in the course of the first visit and then in 2-mo intervals or at the end of observation. Total sperm count was determined in each semen sample. Two to four animals were castrated at weeks 4, 8, 12, 16, 20, 24, 28 and 32 and histologic assessment of the testes was performed. By evaluation of 200 cross sections of seminiferous tubules, the degree of spermatogenic suppression was assessed and animals in Groups 2 and 3 were assigned into groups according to most tubules with the most developed germ cell observed: G1, spermatocytes; G2, round spermatids; G3, elongating spermatids and G4, elongated spermatids. The mean area of Leydig-cell nuclei was calculated. In animals in Group 2, suppression after implant insertion was monitored. T4 concentrations, testis size, and total sperm count gradually decreased (P < 0.01; P < 0.01; and P < 0.05, respectively) within 4 mo after implantation. Histologic evaluation showed a high individual variation in the degree of suppression of spermatogenesis. In animals in Group 3, the implant was removed 4 mo after insertion and the return of sexual activity was monitored. Within 4 mo, T4 concentration and total sperm count increased to the physiological values of intact toms. Testes gradually increased in size and within 4 mo of implant removal almost reached pretreatment size. According to histologic evaluation of the seminiferous tubules, as early as 1 mo after implant removal, all animals were assigned to G4, with most tubules containing elongated spermatids as the most developed germ cells. Treatment with the long-term subcutaneous Gn-RH agonist implant was well tolerated and no adverse treatment-related effects were noted. These results demonstrated efficacy of 4.7 mg deslorelin implant (Suprelorin) with high variability of the effect onset in tomcats. Furthermore, the study revealed a strong need for complex examination, including testis size measurement, monitoring of hormonal changes, spermatological analysis and histologic evaluation, to declare the animal infertile. After the implant removal, all observed parameters confirmed the reversibility of the method and gradual return of sexual activity in toms.
Keywords: Animals; ejakulace; nenasazení léčby; triptorelin-pamoát; Contraceptive Agents, Male; Drug Implants; Organ Size; Testis; testosteron; Withholding Treatment; Contraception; Osmolar Concentration; Recovery of Function; testis; kontraceptiva mužská; Ejaculation; obnova funkce; Cats; Down-Regulation; antikoncepce; osmolární koncentrace; velikost orgánu; Male; implantované léky; Triptorelin Pamoate; Testosterone; down regulace; zvířata; mužské pohlaví; sexuální chování zvířat; Sexual Behavior, Animal; kočky